2018
DOI: 10.1053/j.ajkd.2017.11.016
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Linear Trajectories of Symptoms, Physical Functioning, Cognitive Functioning, Emotional Well-being, and Spiritual Well-being Among Patients Receiving Dialysis

Abstract: Multidimensional patient-reported quality of life varies widely from month to month regardless of whether overall trajectories improve or worsen over time. Additional research is needed to identify the best approaches to incorporate patient-reported outcome measures into dialysis care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 36 publications
2
29
1
1
Order By: Relevance
“…In our study, we assessed functional status only at two time points: at the start and 6 months after start of dialysis. Because functional dependence can vary even in stable dialysis patients (33), more frequent assessments, including the predialysis phase and longer follow-up, are needed to elucidate the full functional trajectory and assess the effect of hospitalization or life events. In this study, we used a cut-off point of 1 as the definition of decline in functional status.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we assessed functional status only at two time points: at the start and 6 months after start of dialysis. Because functional dependence can vary even in stable dialysis patients (33), more frequent assessments, including the predialysis phase and longer follow-up, are needed to elucidate the full functional trajectory and assess the effect of hospitalization or life events. In this study, we used a cut-off point of 1 as the definition of decline in functional status.…”
Section: Discussionmentioning
confidence: 99%
“…We found that mESRD exhibited greater memory than bESRD, but both were worse than HCs. Based on previous research, there were not yet able to provide an uncontested result whether cognition was improved or worsened during dialysis [51][52][53]. Based on the results of the neuropsychological tests, our results seemed to indicate that ESRD patients who underwent long-term dialysis have better cognitive function than ESRD patients before dialysis initiation.…”
Section: Discussionmentioning
confidence: 63%
“…14 Many patients already have partially compromised cognition at dialysis initiation, [15][16][17] which further declines while undergoing treatment, 10,[18][19][20] and often fluctuates from month to month. 21 In fact, only 13% of prevalent HD patients were reported to have normal cognition 22 and clinicians often fail to recognize declining cognition among patients who are undergoing HD 23 or KT. 6 In fact, physicians were found to only accurately identify HD patients and KT recipients 57% 23 and 66% 6 of the time, respectively.…”
Section: Global Cognitive Function Among Patients With Eskdmentioning
confidence: 99%
“…In a cohort study of 324 adults aged 18 years and older initiating HD (mean age = 55), the average (SD) 3MS score for global cognitive function was 89.8 (7.6), which parallels scores of the most cognitively vulnerable group of community‐dwelling older adults aged 60 years and older . Many patients already have partially compromised cognition at dialysis initiation, which further declines while undergoing treatment, and often fluctuates from month to month . In fact, only 13% of prevalent HD patients were reported to have normal cognition and clinicians often fail to recognize declining cognition among patients who are undergoing HD or KT .…”
Section: Introductionmentioning
confidence: 99%